Association between insufficient level of physical activity and multiple health risk behaviors in adolescents - Lucas Souza Santos; Davi Soares Santos Ribeiro; Íkaro Daniel Carvalho Barreto; Vitor Hugo Fernando de Oliveira; Danilo Rodrigues Pereira da Silva; Aldemir Smith Menezes (Universidade Estadual Paulista (UNESP), 2019)
Abstract Aim: To verify the association between insufficient level of physical activity and multiple health risk behaviors (HRB) in adolescents. Methods: This is an epidemiological study with cross-sectional design carried out in 2016 with 3,617 adolescents aged 14-19 years and enrolled in the public-school system of Sergipe, northeast Brazil. Data were collected using the Global School-based Student Health Survey (GSHS/WHO). The insufficient level of physical activity was defined as not achieving at least 60 minutes of moderate to vigorous physical activity for 5 days a week. The HRB analyzed were smoking, alcohol consumption, low fruit consumption and exposure to sedentary behavior. The analysis of prevalence odds ratio was used to identify the association between insufficient level of physical activity and HRB, as well as unadjusted and adjusted binary logistic regression for the association between socioeconomic and demographic variables. Results: The prevalence of insufficient level of physical activity was 83.3%. There was association between physical inactivity and low fruit consumption and alcohol consumption (p<0.001). Insufficient level of physical activity was also associated with female sex (OR=1.90, 95% CI, 1.56-2.32), family income of up to 2 minimum wages (OR=1.57, 95% CI, 1.17-2.11), maternal schooling less than 8 years (OR=1.55, 95% CI, 1.28-1.86) and exposure to two different HRB at the same time (OR=1.76, 95% CI, 1.27-2.45). Conclusion: The prevalence of insufficient level of physical activity is high and was associated with multiple HRBs in this understudied population. These findings may support interventions focusing on the cluster of risk behaviors in youth.